Implementation of Pendidikan Khas Kejogjaan: Preservation of Local Wisdom Through Javanese Karawitan Extracurricular Activities at Elementary Schools - Niswatun, Salisa; Sularso, Sularso; Chabu , Mwansa Edward (Universitas Negeri Surabaya, 2024)
The Pendidikan Khas Kejogjaan integrates local cultural values to prepare students for the Industry 4.0 era. At Kasihan Public Elementary School, the implementation through the extracurricular activity of Javanese karawitan aims to reinforce cultural identity and address the low interest of students in local wisdom. This study aims to describe the implementation and the supporting and inhibiting factors in the preservation of local wisdom through Javanese karawitan extracurricular activities at Kasihan Public Elementary School. Using a qualitative method with a descriptive approach, the study involves the school principal, teachers, and students as subjects. Data was collected through observation, interviews, and documentation, and analyzed using triangulation techniques. The findings indicate that while the facilities are adequate, teachers lack specialized training and student participation is suboptimal due to interest in external cultures. Curriculum planning that integrates local cultural values is effective, but formal teacher training is lacking. The program’s implementation, which includes differentiated learning methods and educational visits, enhances student understanding, although it is hindered by insufficient facilities. Regular evaluations support program improvements. Supporting factors include the involvement of school stakeholders and parental support while inhibiting factors include low student awareness and insufficient teacher skills. The conclusion of this study is that the implementation of Pendidikan Khas Kejogjaan through Javanese karawitan extracurricular activities at Kasihan Public Elementary School is effective in integrating local culture, though it requires better teacher training and facilities. The program enhances students' cultural understanding, supported by systematic evaluations and school stakeholder support, but is impeded by low student awareness and teacher skills. This study’s contribution lies in providing insights into the integration of local cultural values into extracurricular curricula and the factors affecting its success.